INNOVATIVE DEVELOPMENT OF UKRAINE IN THE CONDITIONS OF WAR AND POST-WAR PERIOD - Bohdanna Kosovych (Izdevnieciba "Baltija Publishing", 2022)
The purpose of the research is to reveal the theoretical bases of innovative development, the significance of innovations for the Ukrainian economy, the importance of innovative products in the conditions of war, and the main directions of innovations in the post-war period. The methodological basis of the conducted study is a set of general scientific and special scientific methods, in particular: methods of analysis and synthesis are used to study ideas and existing positions on current approaches to development and components of innovation for the security of the country of the war and the post-war period, method of complex diagnostics - to study the socio-economic prerequisites of successful innovation policy in Ukrainian realities. According to the results of the conducted study, a number of important political, social and economic factors are outlined as components of innovation activity in modern Ukraine, aimed at ensuring national security and successful development of the Ukrainian state. Practical implications. In the conditions of full-scale war, there is a growing need to accelerate innovative activities, scientific and technical developments in the field of military-industrial complex; the political and economic tools for protection of citizens in the conditions of war and post-war reconstruction of Ukraine should be updated. Value/originality. Important role for successful innovation processes is played by economic factors, among which it is expedient to highlight such as: development of military-industrial complex with introduction of the latest technologies, strengthening of state regulation of economy, active attraction of investments, development of science and education, ensuring of social consensus, etc.